2020
DOI: 10.1038/s41436-019-0682-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of 84 PALB2 variants of uncertain significance

Abstract: Inherited pathogenic variants in PALB2 are associated with increased risk of breast and pancreatic cancer. However, the functional and clinical relevance of many missense variants of uncertain significance (VUS) identified through clinical genetic testing is unclear. The ability of patient-derived germline missense VUS to disrupt PALB2 function was assessed to identify variants with potential clinical relevance. Methods: The influence of 84 VUS on PALB2 function was evaluated using a cellular homology directed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 29 publications
12
54
1
Order By: Relevance
“…In the PALB2 N-terminus, p.L35P (c.104T>C) disrupts BRCA1-PALB2 interaction and abolishes the HR activity of PALB2, resulting in sensitivity to the PARPi (106). Moreover, p.P8L (c.23C>T), p.K18R (c.53A>G), p.L24S (c.71T>C), p.Y28C (c.83A>G), and p.R37H (c.110G>A) compromise HR activity of PALB2 and are suggested to be pathogenic (106)(107)(108). In the PALB2 C-terminus, p.W912G, p.G937R, p.L939W, p.I944N (c.2831T>A), p.L947F (c.2841G>T), p.L947S (c.2840T>C), p.L961P, p.L972Q, p.A1025R, p.T1030I (c.3089C>T), p.I1037T, p.G1043D, p.L1070P (c.3209T>C), p.P1088S (c.3262C>T), p.W1140G (c.3418T>C), p.L1143P, and p.L1172P promoted a decrease in the HR activity of PALB2 (20,(107)(108)(109)112).…”
Section: The Challenges Of Palb2 Research In Clinical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PALB2 N-terminus, p.L35P (c.104T>C) disrupts BRCA1-PALB2 interaction and abolishes the HR activity of PALB2, resulting in sensitivity to the PARPi (106). Moreover, p.P8L (c.23C>T), p.K18R (c.53A>G), p.L24S (c.71T>C), p.Y28C (c.83A>G), and p.R37H (c.110G>A) compromise HR activity of PALB2 and are suggested to be pathogenic (106)(107)(108). In the PALB2 C-terminus, p.W912G, p.G937R, p.L939W, p.I944N (c.2831T>A), p.L947F (c.2841G>T), p.L947S (c.2840T>C), p.L961P, p.L972Q, p.A1025R, p.T1030I (c.3089C>T), p.I1037T, p.G1043D, p.L1070P (c.3209T>C), p.P1088S (c.3262C>T), p.W1140G (c.3418T>C), p.L1143P, and p.L1172P promoted a decrease in the HR activity of PALB2 (20,(107)(108)(109)112).…”
Section: The Challenges Of Palb2 Research In Clinical Applicationmentioning
confidence: 99%
“…Moreover, p.P8L (c.23C>T), p.K18R (c.53A>G), p.L24S (c.71T>C), p.Y28C (c.83A>G), and p.R37H (c.110G>A) compromise HR activity of PALB2 and are suggested to be pathogenic (106)(107)(108). In the PALB2 C-terminus, p.W912G, p.G937R, p.L939W, p.I944N (c.2831T>A), p.L947F (c.2841G>T), p.L947S (c.2840T>C), p.L961P, p.L972Q, p.A1025R, p.T1030I (c.3089C>T), p.I1037T, p.G1043D, p.L1070P (c.3209T>C), p.P1088S (c.3262C>T), p.W1140G (c.3418T>C), p.L1143P, and p.L1172P promoted a decrease in the HR activity of PALB2 (20,(107)(108)(109)112). Among these mutations, p.L939W, p.A1025R, p.T1030I, p.P1088S, and p.L1143P disrupt BRCA2-PALB2 interaction; p.W912G, p.G937R, p.I944N, p.L961P, p.L972Q, p.T1030I, p.I1037T, p.G1043D, and p.L1172P are associated with PALB2 protein instability; and p.I944N, p.L947F, p.L947S, p.T1030I, p.L1070P, and p.W1140G result in the mislocalization of PALB2 to the cytoplasm.…”
Section: The Challenges Of Palb2 Research In Clinical Applicationmentioning
confidence: 99%
“…Assays using HR as a read-out have emerged as the standard for the functional characterisation of VUS in BRCA1 and BRCA2 (Bouwman et al, 2013;Woods et al, 2016;Shimelis et al, 2017;Starita et al, 2018;Mesman et al, 2019). More recently, VUS in PALB2 have also been characterized in a similar manner (Figures 1, 2) (Park et al, 2014;Foo et al, 2017;Boonen et al, 2019;Rodrigue et al, 2019;Wiltshire et al, 2019). To identify variants that impact HR, the well described DR-GFP reporter, as well as the more recently introduced CRISPR-LMNA HR assay were used (Kass et al, 2013;Ducy et al, 2019).…”
Section: A Comprehensive Functional Analysis Of Vus In Palb2mentioning
confidence: 99%
“…PALB2-interacting proteins are depicted underneath their respective PALB2 interacting domain/regions. All PALB2 genetic variants from five functional studies (Park et al, 2014;Foo et al, 2017;Boonen et al, 2019;Rodrigue et al, 2019;Wiltshire et al, 2019) are shown and categorized per (functional) domain as benign (green framed sections), truncating (red framed sections), or VUS and synthetic missense variants (MVs) (blue framed sections) based on ClinVar. All functionally damaging PALB2 VUS with an HR efficiency < 50% compared to wild type PALB2 in at least one functional assay are highlighted in red.…”
Section: A Comprehensive Functional Analysis Of Vus In Palb2mentioning
confidence: 99%
See 1 more Smart Citation